Effects of Interspecific Grafting Between Capsicum Species on Scion Fruit Quality Characteristics - Andrey Vega-Alfaro (American Society for Horticultural Science (ASHS), 2021)
Production of Capsicum annuum peppers is often limited, especially in tropical environments, by susceptibility to soil pathogens including Ralstonia solanacearum. Grafting desirable cultivars onto selected rootstocks can increase adaptation to abiotic stress and is an alternative to pesticides for managing soilborne pathogens. Cultivars of two other pepper species, Capsicum baccatum and Capsicum chinense, are tolerant or resistant to an array of soilborne pathogens and have potential as rootstocks; however, knowledge of how interspecific grafting may affect scion fruit quality is lacking. Flowering time, yield, and fruit quality characteristics were evaluated in 2017 and 2020 for C. annuum cultivars Dulcitico, Nathalie (2017), Gypsy (2020), and California Wonder used as scions grafted onto Aji Rico (C. baccatum) and Primero Red (C. chinense) rootstocks, including self-grafted and nongrafted scion checks. In 2020, the rootstocks per se were evaluated. The two rootstocks (‘Aji Rico’ and ‘Primero Red’), three scions, and self- and nongrafted scions were evaluated using a factorial, replicated, completely randomized design in fields at the West Madison and Eagle Heights Agricultural Research Stations located in Madison, WI, in 2017 and 2020, respectively. Differences among the main effects for scion fruit quality characteristics were consistent with cultivar descriptions. No scion × rootstock interactions were observed. Rootstocks did not result in changes in total fruit number, yield, fruit shape (length-to-width ratio), or soluble solids of scion fruit compared with self- and nongrafted checks. The rootstock ‘Primero Red’ increased fruit weight and decreased time to flowering regardless of scion compared with self- and nongrafted checks. All scions were sweet (nonpungent) cultivars and both rootstocks were pungent cultivars. No capsaicinoids were detected in the fruit of sweet pepper scions grafted onto pungent pepper rootstocks. The results indicate that interspecific grafts involving ‘Aji Rico’ and ‘Primero Red’ will not have deleterious effects on fruit quality characteristics of sweet pepper scions.